Straw Degradation Behaviors under Different Conditions of Relative Air Humidity and Ultraviolet-A Irradiation - Yunlong Li; Hongying Huang; Guofeng Wu; Zhizhou Chang (BioResources, 2016)
In this study, straw was degraded continuously for 150 days under one of three levels of relative air humidity (RH) (90%, 60%, or 30%) to estimate the effect of humidity on straw biodegradation. Moreover, straw was treated with ultraviolet (UV)-A irradiation + 90% RH for 180 days to evaluate the interaction between photodegradation and biodegradation. The effects of 30% and 60% RH on straw degradation was inconspicuous. Straw mass losses at 90% RH and UV-A + 90% RH were 18.5% and 39.1%, respectively. BIOLOG analysis showed that filamentous fungi played a major role in straw biodegradation. Thermogravimetric analysis showed that treatment with UV-A + 90% RH tended to increase the maximum pyrolysis rate and decreased the initial pyrolysis temperature. Compared with 90% RH, infrared spectra analysis showed that functional groups of UV-A + 90% RH treatment, e.g., –CH, –C=O, and the benzene ring structure, clearly decreased. Straw-degrading bacteria were observed by scanning electron microscopy at the beginning and end of UV-A + 90% RH treatment. Results highlight the role of humidity in the degree of straw biodegradation by filamentous fungi. Straw degradation is accelerated by the combined action of photodegradation and biodegradation under high UV-A irradiation and high humidity.